ON THE GENERALIZED WEIGHTED STATISTICAL CONVERGENCE - Bektaş, Çiğdem A.; Bayram, Erdal (My University, 2024)
Statistical convergence and summability represent a significant generalization of traditional convergence for sequences of real or complex values, allowing for a broader interpretation of convergence phenomena. This concept has been extensively examined by numerous researchers using various mathematical tools and applied to different mathematical structures over time, revealing its relevance across multiple disciplines. In the present study, a generalized definition of the concepts of statistical convergence and summability, termed (?_v^m )_u-generalized weighted statistical convergence and (?_v^m )_u-generalized weighted by [¯N_t ]-summability for real sequences, is introduced using the weighted density and generalized difference operator. Based on this definition, several fundamental properties and inclusion results, obtained by differentiating the components used in the definitions, are provided.
Keywords: Weighted density; Generalized difference sequence; Weighted statistical convergence; Weighted summability